Chemotaxis-driven assembly of endothelial barrier in a tumor-on-a-chip platform. Issue 10 (21st April 2016) - Aung, Aereas; Theprungsirikul, Jomkuan; Lim, Han Liang; Varghese, Shyni
Abstract : Chemotaxis-driven assembly of an endothelial barrier around tumor cells within a microfluidics device. Abstract : The integration of three-dimensional micropatterning with microfluidics provides a unique opportunity to create perfusable tissue constructs in vitro . Herein, we have used this approach to create a tumor-on-a-chip with an endothelial barrier. Specifically, we photopatterned a mixture of endothelial cells and cancer spheroids within a gelatin methacrylate (GelMA) hydrogel inside a microfluidic device. The differential motility of endothelial and cancer cells in response to a controlled morphogen gradient across the cell-laden network drove the migration of endothelial cells to the periphery while maintaining the cancer cells within the interior of the hydrogel. The resultant endothelial cell layer forming cell–cell contact via VE-cadherin junctions was found to encompass the entire GelMA hydrogel structure. Furthermore, we have also examined the potential of such a tumor-on-a-chip system as a drug screening platform using doxorubicin, a model cancer drug.